2020
DOI: 10.34172/aim.2020.102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of 905 COVID-19 Patients Admitted to Imam Khomeini Hospital Complex in the Capital City of Tehran, Iran

Abstract: Background: We studied the clinical characteristics and outcomes of 905 hospitalized coronavirus disease 2019 (COVID-19) patients admitted to Imam Khomeini Hospital Complex (IKHC), Tehran, Iran. Methods: COVID-19 patients were recruited based on clinical symptoms and patterns of computed tomography (CT) imaging between February 20 and March 19. All patients were tested for the presence of COVID-19 RNA. The Poisson regression model estimated the incidence rate ratio (IRR) for different parameters. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 37 publications
5
26
4
1
Order By: Relevance
“… 16 21 However, others could not find a relationship between sex, mortality, and other unfavorable outcomes in COVID-19. 17 , 18 In the present study, mortality was similar between male and female patients. Although the prevalence of AKI and smoking was lower in women, the need for ICU, intubation, and mechanical ventilation was similar between male and female patients.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“… 16 21 However, others could not find a relationship between sex, mortality, and other unfavorable outcomes in COVID-19. 17 , 18 In the present study, mortality was similar between male and female patients. Although the prevalence of AKI and smoking was lower in women, the need for ICU, intubation, and mechanical ventilation was similar between male and female patients.…”
Section: Discussionsupporting
confidence: 64%
“…Fever was the most common (90%) symptom in our patient population, similar to other studies (frequency reported between 77.4–98.6%. 1 18 There are limited data showing an association between fever (body temperature) and mortality. A retrospective analysis of 9417 patients showed that low (<36°C) body temperature (BT) on admission was significantly associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…observed no significant differences in in-hospital mortality between patients treated with HCQ with or without azithromycin and patients who received neither drugs. [ 38 39 40 ] Lee et al . studied several observational studies and two huge randomised control trials and suggested that HCQ does not offer efficacy against hospitalised COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying patients at high risk of disease progression may help allocating resources more efficiently. Since presentation and course of the infection can vary considerably (including asymptomatic cases), no single trait is sufficient to appropriately categorise patients [1][2][3][4][5][6][7][8][9]. Thus, several scores have attempted to improve identification of patients at high risk of progression or death of COVID-19.…”
Section: Introductionmentioning
confidence: 99%